2011
DOI: 10.1016/j.actatropica.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Mansonella perstans filariasis in Africa

Abstract: Mansonella perstans is a vector-borne human filarial nematode, transmitted by tiny blood-sucking flies (biting midges). It is widespread in many parts of Sub-Saharan Africa and also occurs in parts of Central and South America. Despite the commonness of this parasite very few studies have been carried out on its epidemiology and on the morbidity resulting from it, and only few thorough drug trials have been conducted to look for effective and suitable drugs and drug regimens for treatment and control. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(241 citation statements)
references
References 97 publications
3
221
4
3
Order By: Relevance
“…A history of ivermectin treatment for onchocerciasis was found in both cases and controls. Evidence of infection with Mansonella perstans, another insect vector-borne human filarial nematode, 28 was also significantly higher in cases than controls. By contrast, there was no difference in infection with Wucheria bancrofti, the nematode responsible for lymphatic filariasis.…”
Section: -2002mentioning
confidence: 93%
“…A history of ivermectin treatment for onchocerciasis was found in both cases and controls. Evidence of infection with Mansonella perstans, another insect vector-borne human filarial nematode, 28 was also significantly higher in cases than controls. By contrast, there was no difference in infection with Wucheria bancrofti, the nematode responsible for lymphatic filariasis.…”
Section: -2002mentioning
confidence: 93%
“…A remarkably diminished difference in NATOG concentration with high statistical significance (4.2 ± 0.7 μM; P < 0.001) was observed. Although these data suggest a metabolic specificity of NATOG for O. volvulus and the host, future sampling of other human filarial nematode species, such as Loa loa and Mansonella perstans, will help to establish a more complete picture of the metabolic regulation of NATOG and these other parasitic disease states (20).…”
Section: −8mentioning
confidence: 99%
“…The quality control indicated that some laboratory technicians had difficulty differentiating W. bancrofti from Mansonella perstans , a much more common filarial parasite. 10 To make sure that no positive slides were missed, it was decided, after the first year's activities, that all slides would be reread.…”
Section: Methodsmentioning
confidence: 99%